A traceless clean-up method coupled with gas chromatography and mass spectrometry for analyzing polycyclic aromatic hydrocarbons in complex plant leaf matrices. Issue 9 (1st April 2020) - Jin, Xiangzi; Kaw, Han Yeong; Li, Huijie; Zhao Wang,; Zhao, Jinhua; Piao, Xiangfan; Li, Donghao; Jin, Dongri; He, Miao
Abstract : This study developed a traceless clean-up method by combining solid phase extraction (SPE) with gas purge–microsyringe extraction (GP–MSE) to purify sample extracts for the determination of polycyclic aromatic hydrocarbons (PAHs) in plant leaves. Abstract : This study developed a traceless clean-up method by combining solid phase extraction (SPE) with gas purge–microsyringe extraction (GP–MSE) to purify sample extracts for the determination of polycyclic aromatic hydrocarbons (PAHs) in plant leaves. SPE exhibited good purification performance for the removal of polar lipids, while the GP–MSE technique effectively eliminated less-volatile lipids hence realizing zero damage to the instrument, and significantly improved the peak tailings. After ultrasonic extraction, the combined two-step clean-up procedure successfully removed over 99% of lipids from nineteen types of tree leaves, and PAHs in tree leaves were determined by GC–MS. The relative standard deviations (RSDs) for intra-day ( n = 3) and inter-day ( n = 3) analyses of PAHs in spiked willow samples were in the range of 0.8%–12.1% and 4.7%–15.3%, respectively. The recoveries of PAHs from spiked willow extracts ranged from 74 to 90%, with an average of 86%. The method detection limit (MDL) of PAHs in tree leaves ranged from 0.1 to 4.9 ng g −1 dry weight. In conclusion, the clean-up method in this study realized the analysis of PAHs in plant leaves with high accuracy, sensitivity and reproducibility. Most importantly, the two-step purification method significantly minimizes damage to the GC–MS system particularly to the column and ion source, which is beneficial to ensure continuous analysis of a large number of samples with good performance.